2014
DOI: 10.9790/0853-13315461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluated of Testicular Tumors using Doppler Sonography

Abstract: This study aimed to determine the gray scale and color Doppler sonographic features of the most common and some of the least common scrotal lesions. Between October 2012 to May 2013, 100 patients the age range of new born to 85 years old the mean 30.95, with scrotal symptoms, who underwent scrotal ultrasonography (US), were retrospectively reviewed. The clinical presentation, outcome, and US results were analyzed. The presentation symptoms including scrotal pain, painless scrotal mass or swelling, and trauma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Likewise, Necas M et al [11] found that the patients were on average 39 years old. On the other hand, The average age of the patients was 30.95 years, according to Hamdan A et al [10]. Assi T et al [12] found that testicular tumor patients were on average 32 years old.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, Necas M et al [11] found that the patients were on average 39 years old. On the other hand, The average age of the patients was 30.95 years, according to Hamdan A et al [10]. Assi T et al [12] found that testicular tumor patients were on average 32 years old.…”
Section: Discussionmentioning
confidence: 98%
“…It's a useful screening and diagnostic tool, and it aids in determining how to proceed in the right therapeutic environment. [10]. Testicular cancer is the most frequent malignancy in young adolescent and adult boys.…”
Section: Discussionmentioning
confidence: 99%